2015
DOI: 10.3892/mmr.2015.3743
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lymphatic metastasis-associated genes in a metastatic ovarian cancer cell line

Abstract: Abstract. Ovarian cancer (OC) is the gynecological malignancy with the highest rate of mortality, and lymphatic metastasis is a critical factor in disease recurrence and prognosis. In the current study, the SKOV-3/LN403 cell line, which has high potential for lymph node metastasis was established as a result of four rounds of selection from retroperitoneal lymph nodes following intraperitoneal injections of SKOV-3 ovarian adenocarcinoma cells. In comparison to the parental SKOV-3 cell line, SKOV-3/LN403 has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…SKOV-3 cells, established from a human ovarian adenocarcinoma, were obtained from the Shanghai Institute of Cell Biology of the Chinese Academy of Sciences (Shanghai, China). The SKOV-3-LN subline, which has the potential to induce higher rates of lymphatic metastasis, peritoneal dissemination and bloody ascites, was established previously in our laboratory ( 17 ). Cells were grown in McCoy's 5A medium (Hyclone; GE Healthcare Life Sciences, Logan, UT, USA) and were supplemented with 10% (v/v) fetal bovine serum (Thermo Fisher Scientific, Inc., Waltham, MA, USA), 100 U/ml penicillin, and 100 µg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…SKOV-3 cells, established from a human ovarian adenocarcinoma, were obtained from the Shanghai Institute of Cell Biology of the Chinese Academy of Sciences (Shanghai, China). The SKOV-3-LN subline, which has the potential to induce higher rates of lymphatic metastasis, peritoneal dissemination and bloody ascites, was established previously in our laboratory ( 17 ). Cells were grown in McCoy's 5A medium (Hyclone; GE Healthcare Life Sciences, Logan, UT, USA) and were supplemented with 10% (v/v) fetal bovine serum (Thermo Fisher Scientific, Inc., Waltham, MA, USA), 100 U/ml penicillin, and 100 µg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Another study was performed to characterize the patterns of expression of the ubiquitin-specific protease 7 (USP7); it was found that high expression of USP7 significantly correlated with lymph node metastases [ 116 ]. Upregulation of focal adhesion kinase (FAK) in EOC cells strongly correlated with incidence of lymph node metastases as well [ 117 ].…”
Section: Mechanisms Regulating Lymphatic Metastasis From Eocmentioning
confidence: 99%